PANDEMI COVID-19: KEPUASAN SISWA DALAM PEMBELAJARAN DARING MELALUI PENGUASAAN TEKNOLOGI DAN MOTIVASI BELAJAR - Wienda Gusta; Neviyarni Suhaili; Mudjiran; Herman Nirwana; Zakirman (Universitas Terbuka, 2022)
This research aims to find out the level of student satisfaction reviewed from the mastery of technology and learning motivation of SMKN 8 Padang students. The research data was collected through the dissemination of questionnaires using a 5-point likert scale. There were 108 students selected using cluster random sampling, a data validity technique performed with a total correlation corrected item test. Data analysis used multiple linear regression analysis with SPSS version 23.0 for data processing. The results of this study prove that the mastery of technology and learning motivation partially and simultaneously affects the student satisfaction of SMKN 8 Padang positively and significantly.